Engaging Adolescent Learners International Perspectives on Curriculum, Pedagogy and Practice - Yee, Brandy (Springer International Publishing, 2018)
This book draws on detailed case studies from three very different countries and school systems to explore the early adolescent learner and the middle years of learning, both of which are often overlooked in the literature. An abundance of research shows the importance of the middle years in putting early adolescent learners on the path to success in further education, careers, and general wellbeing. By focusing on bringing current research to life through the sharing of practical examples and lived experiences of practitioners, this book explores how issues such as curriculum reform, inclusive philosophies, instructional design, and assessment practices are supporting the conditions in which effective middle years learning can unfold. A comparative approach, using data from Canada, Germany and Finland, is utilized to critically examine the effects of the pedagogical methods employed by teachers, and the learning environments in which formal education takes place. The book makes a compelling case for the importance of fostering student voice and choice, and developing new ways of engaging the school community as a whole, and makes a valuable contribution to the discourse concerning early adolescent learners and the middle years of schooling. .